South Africa : 2013 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that South Africa's economy has underperformed other emerging markets and commodity exporters, exacerbating South Africa's already-high levels of unemployment (25 percent) and inequality, and contributing to rising social tensions. At the same time, weak trading partner growth, coupled with declining competitiveness and countercyclical fiscal policy, have led to rising fiscal and current account deficits and made South Africa vulnerable to a prolonged reversal of capital inflows. The outlook is for continued sluggish growth and elevated current account deficits. Growth is projected at 2 percent in 2013 as weak consumption growth and lackluster private investment offset robust public investment and higher export growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet